Developing a Proactive Model to Assess Safety and Health Performance in Electrical and Electronic (E&E) Manufacturing Industries - Lee, Chia Kuang; Noor Azlinna, Azizan; Fadzida, Ismail; Nurhaizan, Mohd Zainudin (2013)
Manufacturing industry in Malaysia plays a prominent role in generating our nation’s income and economic growth and has a large influence in the country's economy. Yet; accident rate in manufacturing industry in Malaysia is alarmingly high. To assess the current safety performance on working place in manufacturing industry, there is a need to have an attempt of measurement to convert current performance into future improvements. Since the Electrical & Electronic Manufacturing (E&E) Industry is the leading sector in Malaysia’s manufacturing industry; the aim of this paper is to propose the development and methodology of a proactive safety and health performance measurement tool for E&E manufacturing industry. In response to this need, OMAX or known as Objective Matrix can be utilized as a score card to assess and evaluate and look into how safe the working place is. OMAX was developed to measure work-unit performance in service industries and enables the user to specify performance criteria, generate a performance scale for each criterion and assign weights to all criteria. To establish weights for OMAX, Analytic Hierarchy Process will be adopted as an approach in determining the weights for the critical factors that affect safety performance of E&E manufacturing industry. Wide and vigorous survey will be carried out to identify the critical factors that influence safety performance in manufacturing industry. Once the critical factors has been established, another survey will be done to obtain the respondents’ feedback on the priority of the factors , and by applying Analytic Hierarchy Process (AHP), the weights of the factors can thus be identified for OMAX. Finally, the complete OMAX will be transcribed into computer programme interface developed with Microsoft Visual Studio 2005 with C# as the programming language. Optimistically, the proposed model will yield a proactive safety and health performance measurement tool to improve any inadequacy of safety aspects in managing safety in Malaysian E&E manufacturing industry.